FAKTOR-FAKTOR YANG MENDASARI MASYARAKAT SEKITAR TAMAN NASIONAL MERU BETIRI MENGAMBIL RAFFLESIA Zollingeriana Kds. - Nurlela Fatmawati; Mustapit Mustapit; Sofia Sofia (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Rafflesia zollingeriana Kds. is the only endemic Rafflesia species in Meru Betiri National Park. The threatened status is on endangered. But, the people who resident in around of forest belief this plant have a savour in health as traditional medicine and threatened by theft. The purpose of the research is to knows a). Perceptions of the community around Meru Betiri National Park to Rafflesia zollingeriana Kds. b). Affecting factor the community take Rafflesia zollingeriana Kds. in Meru Betiri National Park area. and c). Actors involved in the activities of the Rafflesia zollingeriana Kds. This research did at Bandealit and Wonosari resort by qualitative method. The results showed that the perception of society is divided into two: economic and social aspects. On the economic aspect, people consider that this plant has a high selling value and can help increase revenue. Based on the social aspect, the daily life of the community around the area is so close from the forest. The main factor that affecting the people around Meru Betiri National Park takes Rafflesia zollingeriana kds. is a factor of economic necessity and social life. Supporting factors is couses the low knowledge of conservation efforts, Low educational, and cultural factors of society who still use traditional medicine as an alternative treatment. The actors involved in taking Rafflesia zollingeriana kds. are buyers, community takers, processors, and sellers.